Fuzzy Prime Ideals of ADL's - Sundar Raj, Chigurupalli Santhi; Amare, Natnael Teshale; Swamy, Uppasetti Madana ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2018)
In this paper the concept of prime L-fuzzy ideals and L-fuzzy prime ideals of an ADL A with truth values in a complete lattice L satisfying the infinite meet distributive law are introduced. All prime L-fuzzy ideals of a given ADL A are determined by establishing a one-to- one correspondence between prime L-fuzzy ideals of an ADL A and the pairs (P;a), where P is a prime ideal of A and a is a prime element in L. Also, here minimal prime L-fuzzy ideals and L-fuzzy minimal prime ideals of an ADL A are introduced and characterized.